Th17–Related Interleukins and Parameters of Oxidative/Nitrosative Events in Childhood Asthma : Interlevkini, povezani s Th17, in parametri, povezanimi z dušikovim oksidom pri astmi otrok - Fabian, Elisabeth; Pölöskey, Peter; Kósa, Lajos; Elmadfa, Ibrahim; Attila Réthy, Lajos (Acta Medico-Biotechnica, 2021)
Purpose: Allergic asthma is a chronic lung disease with a major inflammatory component including reactive oxygen and nitrogen species in the background. The objective of this study was to investigate the relationship between the Th17-associated interleukins IL-6 and IL-10, and oxidative/nitrosative markers of stress in childhood atopic asthma. Methods: For this observational study 35 asthmatic (AG) and 21 healthy (CG) children were recruited; the volume of fractionated exhaled nitric oxide (FENO) was measured with the NIOX nitric oxide monitoring system. Plasma levels of IL-6 and IL-10 were analysed with ELISA, malondialdehyde (MDA) with HPLC. Results: Compared to healthy controls, asthmatics exhaled a significantly (p<0.001) higher mean volume of FENO and had significantly (p=0.012) enhanced levels of IL-6. A significant correlation between the Th17 activator IL-6 and FENO could be found in the asthma (p=0.005) but not in the control group. The plasma concentration of IL-10 was significantly (p=0.002) lower in asthmatics than in controls and correlated significantly negatively with FENO in both groups (AG:p=0.020; CG:p=0.008). Plasma levels of MDA, a lipid peroxidation product and indicator of oxidative stress, were significantly (p<0.001) enhanced in asthmatics. There was a significant (AG:p=0.001; CG:p=0.005) correlation between MDA and IL-6 but not of IL-10 in both groups. Conclusion: This study indicates a significant relationship between the Th17-related cytokines IL-6 and IL-10, pulmonary inflammation, and systemic oxidative stress in asthmatic children. The mechanisms involved in this process have not been fully elucidated an altered redox balance may, however, have considerable influence on asthmatic immunopathology.